Greek military nursing officers' compassion competence and compassion level at work and their professional quality of life - Klimentidou, Thomai; Patsopoulou, Anna; Tzenetidis, Vasileios; Sarafis, Pavlos; Apostolakis, Ioannis; Malliarou, Maria (My University, 2023)
Aim: Of this study was to investigate the level of Military Nursing Officers'(MNOS) compassion competence and their personal level of compassion at work and their correlation with the professional quality of life.
Keywords: Compassion at work; Compassion competence; Military Nurse; Professional Quality of Life